KANDUNGAN GIZI DAN SIFAT FISIK TEPUNG AMPAS KELAPA SEBAGAI BAHAN PANGAN SUMBER SERAT - Putri, Meddiati Fajri (Jurusan Teknologi Jasa dan Produksi, Fakultas Teknik, Universitas Negeri Semarang, 2010)
Fiber intake becomes increasingly take precedence in making the formulationof food products for its role in speeding up digestion, where the bacteria grow duringdiusus and reduce the availability of cholesterol. Utilization of by-product of coconuthusks as a substitute material for health food has not been much revealed. Althoughcoconut pulp is a byproduct manufacture the coconut milk, but coconut pulp is a sourceof food fiber. Coconut pulp derived from a byproduct of the commodity which has theadvantage as a supporter of sustainable food security. This is supported by highproduction potential, process and equipment used in a simple and inexpensiveproduction, has the ability to be processed into products of higher quality, can be addedto bread products, recipes, and food products others as a health food that can supportdiversivikasi food. Nutrient coconut pulp flour contains carbohydrates in a lower amountis about 33.64125 percent, of flour (73.52 percent). Flour protein content of coconut pulpis relatively low at 5.78725 percent, rather than wheat flour (13.51 percent). Fat contentof coconut flour is high enough residue from flour (38.2377 percent). Crude fiber flourcoconut pulp is high enough (15.068865) per cent, higher than wheat flour (0.25percent). Content of insoluble fiber foods are very high (63.66%), and (soluble fiber foodis very low 4.53%, Raghavendra et al, 2004). Flour coconut pulp is one of the flour as asource of food and fiber, coconut husks flour contains water that is low enough to6.9969 percent lower than in wheat flour (11.31 percent). degree of coconut pulp andwhite flour whiter than white flour with a round shape with a range of granule sizes ÃË60-ÃË140 ÃÂ¼m, and granule forms fragments with a range of sizes ÃÅ¾140-300 ÃÂ¼m. Gelconsistency coconut pulp flour has a very weak gel consistency and viscosity of flourpaste coconut pulp is low, NKA flour with coconut husks for 94.62% and 0.34% for theNPAKeywords: Nutrient, physical properties, flour coconut pulp, fiberAsupan serat menjadi semakin diutamakan dalam membuat formulasi produkpangan karena perannya dalam memperlancar pencernaan, tempat berkembang bakteriselama diusus dan mengurangi ketersediaan kolesterol. Pemanfaatan hasil sampingampas kelapa sebagai bahan substitusi makanan kesehatan selama ini belum banyakterungkap. Meskipun ampas kelapa merupakan hasil samping pembuatan santan,namun ampas kelapa merupakan bahan pangan sumber serat. Ampas kelapa berasaldari komoditi hasil samping yang memiliki keunggulan sebagai pendukung kelestarianketahanan pangan. Hal tersebut ditunjang oleh potensi produksi yang tinggi, proses danperalatan yang digunakan dalam produksinya sederhana dan murah, memilikikemampuan untuk diolah menjadi produk-produk yang lebih berkualitas, dapatditambahkan pada produk-produk roti, resep-resep masakan, dan produk-produkmakanan lainnya sebagai makanan kesehatan sehingga dapat menunjang diversivikasipangan. Kandungan gizi tepung ampas kelapa mengandung karbohidrat dalam jumlahyang lebih rendah yaitu sekitar 33,64125 persen, dari tepung terigu (73,52 persen).Kandungan protein tepung ampas kelapa relative cukup rendah yaitu 5,78725 persen,daripada tepung terigu (13,51 persen). Kandungan lemak tepung ampas kelapa cukuptinggi dari tepung terigu (38,2377 persen). Kandungan serat kasar tepung ampas kelapacukup tinggi yaitu (15,068865) persen, lebih tinggi dari tepung terigu (0,25 persen).Kandungan serat pangan tak larut sangat tinggi yaitu (63,66%), dan (serat pangan larutsangat rendah 4,53% ,Raghavendra et al, 2004). Tepung ampas kelapa merupakansalah satu tepung sebagai sumber serat pangan dan tepung ampas kelapamengandung air cukup rendah yaitu 6,9969 persen lebih rendah dari pada tepung terigu(11,31 persen). derajat putih tepung ampas kelapa lebih putih daripada tepung terigu dengan bentuk granula bulat dengan kisaran ukuran ÃË60-ÃË140 ÃÂ¼m dan bentuk granulaserpihan dengan kisaran ukuran ÃÅ¾140-300 ÃÂ¼m. Konsistensi gel tepung ampas kelapamempunyai konsistensi gel sangat lemah dan viskositas pasta tepung ampas kelaparendah, dengan NKA tepung ampas kelapa sebesar 94,62 % dan NPA sebesar 0.34%Kata kunci: Kandungan gizi, sifat fisik, tepung ampas kelapa, serat